Measurement of Uniformity and Multiple Head Registration (MHR)/Centre of Rotation (COR) of a Newly Installed Hybrid SPECT/CT At INMAS, Mymensingh - Uddin, Md Fakhar; Islam, SM Moinul; Khan, M Nasim; Chakraborty, Ratan Kumar; Rima, Shakila Zaman; Ara, Rawshan; Nahar, Nazmun; Khatun, Rajada (Bangladesh Journal of Nuclear Medicine, 2015)
The main quality controls of hybrid SPECT/CT are Uniformity and Multiple Head Registration (MHR)/Centre of rotation (COR). Uniformity corrects and verifies cameras response to uniform distribution of radionuclides on the detector surface. MHR/COR not only observes mechanical errors but also quantitatively corrects the errors due to movement of patients and detectors onthe SPECT images. The aim of the study is to establish baseline values thatcan be used as reference for future quality assurance and to verify the manufacturers specification. Both intrinsic and extrinsic Uniformity were measured by using 18?Ci 99mTc point source and 35mCi 99mTc flood source respectively. For MHR/COR measurements, MHR Phantom containing five approximately equal strength (1 mCi99mTc of each) point sourceswere used. The values were found to be in correlation with manufacturers specification. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22494 Bangladesh J. Nuclear Med. 17(1): 67-74, January 2014